Exudative Polymorphous Vitelliform Retinopathy: Importance of Early Recognition of the Condition in Patients with Metastatic Melanoma. Issue 1 (June 2016) - Lincoff, Norah; Nadeem, Muhammad; Younus, Zilfah; Thirkill, Charles
Abstract Introduction Because of the advent of monoclonal antibodies in the treatment of metastatic melanoma, patients with this disease are surviving longer. Early recognition of the disease has therefore become even more important. Case report We present a patient with vitelliform maculopathy, a paraneoplastic retinal maculopathy that is under-recognized. Clinically the retinal findings of serous detachments and pigmentary macular changes are remarkable, while at the same time these patients have surprisingly very few symptoms. This is in contrast to patients who develop melanoma associated retinopathy (MAR) who are very symptomatic early in the disease, but with more subtle retinal findings. Conclusion Monoclonal antibody treatment is changing the survival rates in metastatic disease making early diagnosis even more important. Exudative polymorphous vitelliform maculopathy (EPVM) needs to be recognized early to avoid delay in diagnosis of metastatic disease.